Design of a prospective clinical study on the agreement between the Continuous GlucoseMonitor, a novel device for CONTinuous ASSessment of blood GLUcose levels, and the RAPIDLab® 1265 blood gas analyser: the CONTASSGLU study - Zimmermann, Johannes B.; Lehmann, Monika; Hofer, Stefan; Hüsing, Johannes; Alles, Catharina; Werner, Jens; Luntz, Steffen P.; Motsch, Johann; Weigand, Markus A. (BMC anesthesiology, 2012)
Although a device is needed to continuously measure blood glucose levels within an intensive care setting, and several large-scale prospective studies have shown that patients might benefit from intensive insulin, potassium, or glucose therapy during intensive care, no devices are currently available to continuously assess blood glucose levels in critically ill patients. We conceived the study described here to evaluate the clinical use of the Continuous Glucose Monitor (CGM) performed via a central vein, and to determine the impact of phenomena, such as drift and shift, on the agreement between the CGM and a RAPIDLab® 1265 blood gas analyser (BGA).
Gesehen am 20.08.2018